Precision measurement of the top-quark mass from dilepton events at CDF II - Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
We report a measurement of the top-quark mass, Mt, in the dilepton decay channel of tt̄→b ′+ν ′b̄ -ν̄ using an integrated luminosity of 1.0fb-1 of pp̄ collisions collected with the CDF II detector. We apply a method that convolutes a leading-order matrix element with detector resolution functions to form event-by-event likelihoods; we have enhanced the leading-order description to describe the effects of initial-state radiation. The joint likelihood is the product of the likelihoods from 78 candidate events in this sample, which yields a measurement of Mt=164.5±3.9(stat.)±3.9(syst.)GeV/c2, the most precise measurement of Mt in the dilepton channel. © 2007 The American Physical Society.